Miniaturized Antenna Design for Dual-Band Wi-Fi 6/6E Applications Using the Ground Radiation Technique - Rui Li; Longyue Qu; Jeonghwan Kim; Huanxuan Ren; Hyung-Hoon Kim; Hyeongdong Kim (Journal of Electromagnetic Engineering and Science)
In this letter, we construct a novel compact multi-resonance antenna structure using the ground radiation technique to achieve the intended target frequencies of 2.4–2.5 GHz and (5.125–7.125 GHz) the Wi-Fi 6/6E dual-band. According to the measurement results, under a 3:1 voltage standing wave ratio, the proposed antenna achieved a bandwidth of 450 MHz (ranging from 2.20 GHz to 2.65 GHz) in the lower band, maintaining an average total efficiency of 60.7% from 2.4 GHz to 2.5 GHz. Furthermore, a bandwidth of 2,640 MHz (ranging from 4.81 GHz to 7.45 GHz) was achieved in the higher band, with the average total efficiency being 53.4% from 5.0 GHz to 7.125 GHz. The measured antenna radiation pattern also showed satisfactory antenna radiation performance. Overall, the proposed antenna displays strong potential for use in mobile communication applications.